(3eTcGI GdCfhGQ ddSGdcjf eSGdc GdCHQGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3UdGM Hf eMeO Hf UdGM Hf Ydi Hf GdMSjf Hf YHO Gddg Hf jMji Hf MeRI s)
(3ChdgG (B:s
(3GdMeO ddg GdMi Gdbjhe GdPi CaGV YdjfG CfhGQkG ef eTcGI GdHQgGf , hChQOfG CeG HYO aEfg HdZfG eSGFd ef JdbGA Gdabjg TgGH GdOjf CMeO Hf Ydi TGaYi ade jJeGdc ai QO GdLhGH s
(3BNQgG (B:s
(3agPG eG CQOfG PcQg ef gPg GdeSGFd hQOJ YdjfG hfMf ai MGd GdSaQ aeG CecffG dgG eWGdYI cJGH hEcJajfG eeG MUd Ydi GdHOjgI Je s
(3CLGH Hg eDdag Ydi TgGH GdOjf CMeO Hf Ydi Hf TGaY GdJgGeis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdESdGejs